Evidence for electron Landau damping in space plasma turbulence - C. H. K. Chen (Nature Portfolio, 2019)
Various physical mechanisms are proposed to explain the heating observed in turbulent astrophysical plasmas. Here, Chen et al. find a signature consistent with one of these mechanisms, electron Landau damping, by applying a field-particle correlation technique to in situ spacecraft data of turbulence in the Earth’s magnetosheath.